Constitutive Modeling for Al–Cu–Mg Alloy in Creep Aging Process - Yang, Y.L.; Zhan, L.H.; Xu, X.L. (Проблемы прочности, 2016)
The aim of this paper is to develop a set of creep aging constitutive equations for Al–Cu–Mg alloys containing plate- or rod-like precipitates. Average length, aspect ratio and relative volume fraction are introduced to quantitatively analyze precipitates evaluation of such alloy in creep aging process. The strong interaction between creep deformation and aging treatment is considered by the intermediate state variables of dislocation density and precipitate characteristic dimension. A unified creep aging constitutive equation is derived, in which the correlations between microscopic characteristics and macroperformances of material are linked by the yield strength of the material. Using AA2124 as subject, a series of uniaxial tensile creep tests are carried out at 185°C for 12 h under different stresses. The material constants within constitutive models are determined with the experimental data. A good agreement between experimental and computed values confirms that the established constitutive equations can well characterize the creep behaviors.